2021
DOI: 10.1002/pmic.202000278
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal proteomic profiling provides insights into host response and proteome dynamics in COVID‐19 progression

Abstract: In managing patients with coronavirus disease 2019 (COVID-19), early identification of those at high risk and real-time monitoring of disease progression to severe COVID-19 is a major challenge. We aimed to identify potential early prognostic protein markers and to expand understanding of proteome dynamics during clinical progression of the disease. We performed in-depth proteome profiling on 137 sera, longitudinally collected from 25 patients with COVID-19 (non-severe patients, n = 13; patients who progressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…Findings suggest a role for PON1 against atherosclerosis and obesity and protective capacity against bacterial, parasitic, and viral infectious diseases (59). Regarding COVID-19, PON1 has been shown to increase in protein levels from nonsevere to severe patients (22) and we found the protein underrepresented in nonsevere and recovered patients, thus suggesting a biomarker for disease recovery. CPB2 appears to have a role in innate immunity through inactivation of complement component C5a, which can induce inflammatory pathways via C5aR receptor (41,61).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Findings suggest a role for PON1 against atherosclerosis and obesity and protective capacity against bacterial, parasitic, and viral infectious diseases (59). Regarding COVID-19, PON1 has been shown to increase in protein levels from nonsevere to severe patients (22) and we found the protein underrepresented in nonsevere and recovered patients, thus suggesting a biomarker for disease recovery. CPB2 appears to have a role in innate immunity through inactivation of complement component C5a, which can induce inflammatory pathways via C5aR receptor (41,61).…”
Section: Discussionmentioning
confidence: 61%
“…characterize host response to SARS-CoV-2 infection in different cohorts from asymptomatic individuals to severe patients. Due to the complexity of COVID-19 symptomatology, this approach contributed to a better understanding of disease mechanisms and symptoms with possible medical complications at different levels and the identification of potential diagnostic/prognostic biomarkers and drug targets (22)(23)(24)(25). The results corroborated previous findings in COVID-19 studies and highlighted how the representation of dysregulated serum proteins and associated BPs increases with COVID-19 disease symptomatology from asymptomatic to severe cases (4-6, 8-13, 18, 22-25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 185 , 186 , 187 In addition, there are certain proteomic analysis studies of exosomes and plasma samples, and found that a variety of cytokines including CRP, lactate dehydrogenase (LDH), procalcitonin (PCT), SAA, angiotensinogen (AGT), IL‐12, PTX3, IGLV3‐19, BNC2, CKAP4, and so on are remarkably upregulated or downregulated during the disease progression, which could serve as potential predictors of progression and mortality, although some cytokines are nonspecific and still need further confirmation. 188 , 189 , 190 , 191 , 192 , 193 , 194 Compared with nonsevere COVID‐19 patients, dysregulation of a variety of apolipoproteins (APOA1, APOA2, APOC1, etc.) in critically ill patients was discovered based on proteomic profiling, although the relationship between these proteins and the disease process needs further explanation.…”
Section: Application Of Proteomics In the Emerging Pandemicmentioning
confidence: 99%